Protocol Comparison for Organic Residue Analyses from Waterproofing Materials and Shards of Roman Archaeological Amphorae - Louise Chassouant (MDPI AG, 2021)
With the aim of addressing the impact of extractive protocols in molecular characterization of ceramic content, sixteen archaeological shards and waterproofing coatings of Roman amphorae were studied to compare the extractive capacities of protocols prevalently mentioned in wine amphorae analysis. A microwave-assisted protocol is developed in order to esterify grape-derivative markers from archaeological pitch and shard. Gas chromatography-mass spectrometry is used to highlight the great capacities of a two-step protocol that combines organic extraction with BF3-etherate complex butylation applied on archaeological shards. Instead, simultaneous alkaline fusion and direct-resin acid-catalyzed butylation are favored for the characterization of waterproofing material. The identification of tartaric acid, together with succinic, fumaric pyruvic and syringic acids provide valuable insights on the archaeological grape-derivative content, possibly wine. Diterpenic markers highlighted Pinus pitch and wood tar, originally used to waterproof the amphorae. Since markers are reliable tools in organic residue analyses, protocols exhibiting high extractive capacities are favored to avoid false conclusions drawn through the absence of markers.